Do princesses make happy campers? - Coyle, Carmela LaVigna; Gordon, Mike, 1948 March 16- (Lanham, Maryland : Taylor Trade Publishing, 2015)
During a family camp-out, a young girl asks many questions about what they will do, how she can help, and what they see and hear.
105238
Keywords: Camping; Families; Princesses; Children's questions and answers; Stories in rhyme; Imagination & Play; Nature & the Natural World; Stories in rhyme; Picture books; Juvenile works